Distortionary fiscal policy and monetary policy goals - Klaus Adam; Roberto M. Billi (Sveriges Riksbank, 2013)
We reconsider the role of an inflation conservative central banker in a setting with distortionary taxation. To do so, we assume monetary and fiscal policy are decided by independent authorities that do not abide to past commitments. If the two authorities make policy decisions simultaneously, inflation conservatism causes fiscal overspending. But if fiscal policy is determined before monetary policy, inflation conservatism imposes fiscal discipline. These results clarify that in our setting the value of inflation conservatism depends crucially on the timing of policy decisions.
Keywords: E52; E62; E63; 330; optimal policy; lack of commitment; conservative monetary policy